PENGARUH MOTIVASI, PENDIDIKAN, PELATIHAN DAN PENGALAMAN KERJA TERHADAP KINERJA GURU SMKN 5 BANJARMASIN - Yuse Harlina; Ahmad Alim Bachri; Maya Sari Dewi (Universitas Lambung Mangkurat, 2019)
This research aims to find out and analyze the influence of motivation (X1), Education (X2), Training (X3) Work Experience (X4) as independent variables either partially or simultaneously to the Teacher Performance (Y) as the dependent variable in SMKN 5 Banjarmasin. This research method using purposive sampling technique with sample of 96 teachers SMKN 5 Banjarmasin. Variable measurement technique Likert scale with a weight scale from 1 to 5. To determine the correlation between the variables X1, X2, X3, and X4 towards Y, multiple linear regression correlation technique was used; and to test the significance level, the form of test deteminasi coefficient test was used ;and F test and t test used using SPSS 16 series. The research concludes that there is a significant positive effect of each variable indenvenden variables simultaneouslyand partially towards the dependent variables. Among the four highest indenvenden variables, the variable Work experience (X4) was the highest variable compared to the independent variables towards teacher performance in SMKN 5 Banjarmasin